China – Afghanistan Trade & Strategic Importance of Wakhan Corridor: An appraisal - Mojawir Ahmad Sadat; Mehreen Hassan; Musanif Zeb, (ASIAN Journal of International Peace & Security (AJIPS), 2023)
At the confluence of four states — Pakistan, China, Tajikistan and Afghanistan—is the Wakhan route, a road which is located in the northeast of Badakhshan province of Afghanistan. As part of the old Silk Road, the corridor has much historical importance which has a long (220km) narrow (16-64km) area between from Pakistan to Tajikistan. Still, there is much promise for tourists and regional connections. The strip of Wakhan is extremely tranquil, with no issues with law and order. Wakhan can benefit from increased trade and businesess particularly for Central Asia republics. Therefore, the research investigates the potential to revitalize the corridor of Wakhan by building road infrastructures. The paper is theory base which is critically analyzed the data by studying the litierature reviews, so based on this approach this paper may provide new insights about the importance of the Wakhan corridor. As an outcome, it finds out the Corridor's geostrategic in light of the evolving regional scenario as the most effective rout for both countries. It also talks about the difficulties in carrying out this concept.